'…I've Found Once the Weight Had Gone Off, I've Had a Few Twinges, But Nothing Like Before'. Exploring Weight and Self‐Management of Knee Pain. (17th July 2013) - Morden, Andrew; Jinks, Clare; Ong, Bie Nio
Abstract Objectives Being overweight or obese is a key risk factor for the onset and exacerbation of knee pain. Policy and clinical guidelines encourage lifestyle changes as part of prevention or supported self‐management. The present study explores how people who have not consulted for knee pain understand weight in relation to joint pain, if and how they self‐manage and potential barriers to doing so. Methods A qualitative investigation was undertaken using repeat in‐depth semi‐structured interviews and diary study. Thirteen participants who self‐reported moderate to severe pain and had not recently consulted their general practitioner for knee pain were recruited to the study. Thematic analysis of data was conducted. Results Participants did not recognize the association between being overweight and the onset of joint pain. The findings illuminate understandings of the effect of weight on joint pain, rationales and strategies for losing weight, and how participants' position responsibility for weight gain and loss. Discussion The present study suggests that clinicians need to account for existing understandings and actions of individuals in relation to weight and joint pain. Supported self‐management and public health interventions need to be individually tailored accordingly. © 2013 The Authors. Musculoskeletal Care published by John Wiley & Sons, Ltd.